IDENTIFIKASI PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI DI SMA NEGERI 16 SURABAYA - SRI WAHYU UTAMI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
ABSTRACT Learning process, a material will be useful to understanding and give a treatment according to the characteristic of the students individually, solve the issue of low sel-actualization of the students, so that an elusive material can be explored with printed materials. The purpose of this research is to know a material which is use in a learning process at SMA Negeri 16 Surabaya in subject of vendor accounting services and reason of the teacher of using the material. And know the worthiness of the material. The types of this research is descriptive research kuantitative approach. Technique of collecting data in this research is using interview and distributing questionnairs feasbility study in material accounting services firm. The research result is showed that the material in accounting services firm XI grade students at SMA Negeri 16 Surabaya are using book and handout. The result of worthiness analysis of material get percentase score for book is get percantase score abtained 90,93%, and handout is get percentase score abstained 86,85%. Key word : using, materials, economic, accounting, SMA